The effect of health education on the level of adolescents' knowledge of reproductive health - Dilma Suzete Bento Alves Pereira; Asri Hidayat; Ismarwati Ismarwati (Indonesian Institute For Counseling, Education and Therapy, 2026)
Adolescent reproductive health knowledge remains a global concern; WHO reports approximately 21 million pregnancies annually among adolescents aged 15–19 years, most of which are unintended. In Timor-Leste, the adolescent fertility rate reaches 33.8 births per 1,000 women aged 15–19, and students' reproductive health knowledge at São José Operario Balide School, Dili, remains low. This study aim to analyze the effect of reproductive health education on adolescents' knowledge before and after the intervention at São José Operario Balide School, Dili, Timor-Leste. This quantitative study employed a pre-experimental one-group pretest–posttest design. A sample of 70 eleventh-grade students aged 15–19 years was selected from a population of 180 students using proportional stratified random sampling. The intervention consisted of reproductive health education delivered through lectures supported by PowerPoint media. Knowledge was measured using a 25-item Guttman-scale questionnaire and analyzed with the Wilcoxon Signed Rank Test, as the data were not normally distributed (Kolmogorov–Smirnov, p < 0.05). Before the intervention, most respondents had poor knowledge (50%), followed by fair (33%) and good (17%). After the intervention, the good category increased to 46%, fair to 36%, while the poor category decreased to 19%. The Wilcoxon test yielded Z = −5.032 with p = 0.000 (p < 0.05), indicating a significant difference in knowledge scores before and after the education. Reproductive health education delivered through lectures supported by PowerPoint media significantly improved adolescents' knowledge, providing a basis for strengthening sustainable school-based reproductive health education programs.